Status of knowledge and practice about complete tetanus toxoid immunization of unmarried female students of a public university in Dhaka (Bangladesh Journal of Medical Science, 2010)
Objective: The present study was undertaken to assess the level of knowledge and practice about tetanus toxoid immunization of a group students from a public university. Materials & Methods: This cross-sectional survey was carried out on 113 female students randomly selected from Dhaka University. The interview was conducted using a structured questionnaire. Results: Mean age of the respondents was 19.7±1.2 years (mean±SD). About 90% of the respondents knew about tetanus. Regarding age groups prone to develop tetanus, 49% respondents told ‘children